Fungal and Plant Phenylalanine Ammonia-lyase - Hyun, Min Woo (The Korean Society of Mycology, 2011)
L-Phenylalanine is one of the essential amino acids that cannot be synthesized in mammals in adequate amounts to meet the requirements for protein synthesis. Fungi and plants are able to synthesize phenylalanine via the shikimic acid pathway. L-Phenylalanine, derived from the shikimic acid pathway, is used directly for protein synthesis in plants or metabolized through the phenylpropanoid pathway. This phenylpropanoid metabolism leads to the biosynthesis of a wide array of phenylpropanoid secondary products. The first step in this metabolic sequence involves the action of phenylalanine ammonia-lyase (PAL). The discovery of PAL enzyme in fungi and the detection of (14)CO(2) production from (14)C-ring-labeled phenylalanine and cinnamic acid demonstrated that certain fungi can degrade phenylalanine by a pathway involving an initial deamination to cinnamic acid, as happens in plants. In this review, we provide background information on PAL and a recent update on the presence of PAL genes in fungi.